Racial differences in colorectal cancer survival at a safety net hospital. (August 2017) - Tapan, Umit; Lee, Shin Yin; Weinberg, Janice; Kolachalama, Vijaya B.; Francis, Jean; Charlot, Marjory; Hartshorn, Kevan; Chitalia, Vipul
Highlights: This study was conducted at a large academic safety net hospital with a sizable proportion of non-White patients with equal access to healthcare. Despite receiving comparable first line treatment and achieving comparable response rates, Black patients demonstrated inferior survival compared to White patients. Aside from health care delivery, this study implicates factors such as pathologic and genetic mediators as important contributors to racial disparity in colorectal cancer survival. Abstract: Background: While racial disparity in colorectal cancer survival have previously been studied, whether this disparity exists in patients with metastatic colorectal cancer receiving care at safety net hospitals (and therefore of similar socioeconomic status) is poorly understood. Methods: We examined racial differences in survival in a cohort of patients with stage IV colorectal cancer treated at the largest safety net hospital in the New England region, which serves a population with a majority (65%) of non-Caucasian patients. Data was extracted from the hospital's electronic medical record. Survival differences among different racial and ethnic groups were examined graphically using Kaplan-Meier analysis. A univariate cox proportional hazards model and a multivariable adjusted model were generated. Results: Black patients had significantly lower overall survival compared to White patients, with median overall survival of 1.9 years and 2.5 years respectively. In a multivariate analysis, Black race posed a significant hazard (HR 1.70, CI 1.01–2.90, p = 0.0467) for death. Though response to therapy emerged as a strong predictor of survival (HR = 0.4, CI = 0.2-0.7, p = 0.0021), it was comparable between Blacks and Whites. Conclusions: Despite presumed equal access to healthcare and socioeconomic status within a safety-net hospital system, our results reinforce findings from previous studies showing lower colorectal cancer survival in Black patients, and also point to the importance of investigating other factors such as genetic and pathologic differences.